Efficacy of epidural steroid injection in the treatment of sciatica secondary to lumbar disc herniation: a systematic review and meta-analysis - Zhang, Jianan; Zhang, Ruimeng; Wang, Yue; Dang, Xiaoqian (Frontiers in Neurology, 2024)
Epidural steroid injection for the treatment of sciatica caused by disc herniation is increasingly used worldwide, but its effectiveness remains controversial. The review aiming to analyze the efficacy of epidural steroid injection on sciatica caused by lumbar disc herniation. Randomized controlled trials (RCTs) investigating the use of epidural steroid injections in the management of sciatica induced by lumbar disc herniation were collected from PubMed and other databases from January, 2008 to December, 2023, with epidural steroid injection in the test group and epidural local anesthetic and/or placebo in the control group. Pain relief rate, assessed by numerical rating scale (NRS) and visual analogue scale (VAS) scores, and function recovery, evaluated by Roland Morris Disability Questionnaire (RMDQ) and Oswestry Disability Index (ODI) scores, were recorded and compared. Meta-analysis was performed by Review Manager. In comparison to the control group, epidural steroid injections have been shown to be effective for providing short-(within 3 months) [MD = 0.44, 95%CI (0.20, 0.68), P=0.0003] and medium-term (within 6 months) [MD=0.66,95%CI (0.09,1.22), P=0.02] pain relief for sciatica caused by lumbar disc herniation, while its long-term pain-relief effect were limited. However, the administration of epidural steroid injections did not lead to a significant improvement on sciatic nerve function in short-[MD=0.79, 95%CI= (0.39, 1.98), P=0.19] and long-term [MD=0.47,95% CI= (-0.86, 1.80), P=0.49] assessed by IOD. Furthermore, the analysis revealed that administering epidural steroid injections resulted in a reduction in opioid usage among patients with lumbar disc herniation [MD = -14.45, 95% CI = (-24.61, -4.29), P = 0.005]. The incidence of epidural steroid injection was low. Epidural steroid injection has demonstrated notable efficacy in relieving sciatica caused by lumbar disc herniation in short to medium-term.Therefore, it is recommended as a viable treatment option for individuals suffering from sciatica.